Predictive factors of neoadjuvant immune checkpoint blockade in melanoma - Melissa Sarver; Michael C. Brown; Kristen E. Rhodin; April K. S. Salama; Georgia M. Beasley (Taylor & Francis Group, 2022)
This review describes the current body of literature and ongoing clinical trials examining neoadjuvant immune checkpoint inhibitors (ICI) for patients with resectable stage III and IV melanoma. Based on prior success in treating metastatic melanoma and as adjuvant therapy, ICIs are being explored in the neoadjuvant setting. There have been initial trials and there are many ongoing trials examining neoadjuvant ICI. Herein, we will review the clinical feasibility and efficacy of various neoadjuvant ICI regimens, explore pathologic and cellular responses, and present factors associated with predictive tumor response.